Penanaman Sikap Nasionalisme Melalui Mata Pelajaran IPS Kelas IV Sekolah Dasar - Muchammad Izzuddin Khoirul Chabiba; Erik Aditia Ismaya; Dwiana Asih Wiranti (PGSD Universitas Muria Kudus, 2022)
This study aims to describe the cultivation of nationalism through social studies subjects in Class V.This study uses a qualitative research with a descriptive approach. Data collection was carried out by observation, in-depth interviews, and documentation. The research was conducted at MI Al Yaisniyah Jekulo Kudus. The object of the research is the cultivation of nationalism through social studies subjects, where the fourth grade teacher and the principal as the facilitator of the research subject are the informants of 23 grade IV students. The data analysis used is data reduction, data presentation, and drawing conclusions.The results showed that the cultivation of nationalism in social studies subjects at MI Al Yasiniyah was found in learning activities through habituation, exemplary/modeling activities. In addition, it was found that there were supporting and inhibiting factors. The supporting factor is in the form of adequate infrastructure facilities so that it is easier to cultivate an attitude of Nationalism, especially if it is supported by the use of learning media. Meanwhile, students' lack of understanding of nationalism is an inhibiting factor. Therefore, in explaining must use simple language.